2008
DOI: 10.1007/s11605-007-0362-1
|View full text |Cite
|
Sign up to set email alerts
|

Enteral versus Parenteral Nutrition after Gastrointestinal Surgery: A Systematic Review and Meta-Analysis of Randomized Controlled Trials in the English Literature

Abstract: The present findings would lead us to recommend the use of EN rather than PN when possible and indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
115
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(125 citation statements)
references
References 94 publications
(90 reference statements)
1
115
0
9
Order By: Relevance
“…Several studies including some meta-analyses examine this topic (Baigrie et al, 1996;Velez et al, 1997;Bozzetti et al, 2001;Mazaki and Ebisawa, 2008). In short, the evidence favours enteral over parenteral nutrition.…”
Section: Enteral Feeding Routesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies including some meta-analyses examine this topic (Baigrie et al, 1996;Velez et al, 1997;Bozzetti et al, 2001;Mazaki and Ebisawa, 2008). In short, the evidence favours enteral over parenteral nutrition.…”
Section: Enteral Feeding Routesmentioning
confidence: 99%
“…Several studies have suggested that following gastrointestinal surgery, enteral nutrition is superior to parenteral nutrition (PN), resulting in a reduced length of hospitalisation and serious postoperative complication rates (McCarter et al, 1996;Velez et al, 1997;Aiko et al, 2001;Gabor et al, 2005;Mazaki and Ebisawa, 2008). However, these benefits are not necessarily reproduced following oesophagectomy.…”
Section: Introductionmentioning
confidence: 99%
“…After many reports were issued on the benefits of enteral nutrition in critically ill patients [2,3], several experimental and clinical studies of gastrointestinal surgery have shown that traditional postoperative oral intake restriction is not based on scientific evidence. A number of recent randomized controlled trials and meta-analyses comparing early enteral nutrition and traditional postoperative fasting after gastrointestinal surgery have concluded that early postoperative enteral nutrition reduces postoperative morbidity (especially infectious complications), mortality, and hospital stay without increasing the risk of gastrointestinal-related complications [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Enteral nutrition is considered to be better than total parenteral nutrition for providing feeding in various clinical settings because it is less expensive, safer and maintains the nutritional, metabolic, immunological and barrier function of the intestines with fewer septic complications [6][7][8][9][10]. Jejunostomy is a surgical procedure by which a tube is situated in the lumen of proximal jejunum, primarily to administer enteral nutrition or sometimes medications and on rare occasion to aspirate intestinal contents.…”
Section: Introductionmentioning
confidence: 99%